Implementasi Material Requirement Planning (MRP) untuk Pengelolaan Laboratorium Politeknik Industri Petrokimia Banten - Tito Alfarizi; Triani Aulya Fitri (Nucleus Journal, 2025)
The availability of materials and equipment plays a crucial role in ensuring the continuity and smoothness of the learning process, especially in practical activities. However, in its implementation, there are still obstacles in the form of the unavailability of systematic instruments to support the decision-making process in purchasing practical materials. As a result, there is often a shortage or out-of-stock of practical materials during the activity, which ultimately hinders the learning process. To overcome this problem, this study applies the Material Requirement Planning (MRP) method as a tool in the process of planning practical material needs. MRP is used to analyze material needs based on the practical activity schedule and the availability of existing stock, so that it can be known more accurately when the right time is to reorder. By implementing the Material Requirement Planning (MRP) method, the decision-making process becomes more structured and efficient. This allows laboratory managers or responsible parties to order practical materials in a timely manner, so that supplies are maintained and practical activities can take place without obstacles